2019
DOI: 10.1158/1078-0432.ccr-18-0790
|View full text |Cite
|
Sign up to set email alerts
|

Combination Paclitaxel and Palbociclib: Results of a Phase I Trial in Advanced Breast Cancer

Abstract: Purpose: The CDK 4/6 inhibitor palbociclib rapidly and reversibly inhibits the cell cycle. The goal of this study was to exploit the cell cycle through intermittent, alternating dosing with palbociclib/paclitaxel to enhance efficacy. We determined the combination dose-limiting toxicity (DLT) in patients with Rb protein-expressing, advanced breast cancer. Patients and Methods: This open-label, phase I trial (NCT01320592) enrolled patients to sequential cohorts of palbociclib orally dosed intermittently between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Paclitaxel treatment resulted in apoptosis of cancer cells both In vitro and In vivo conditions [35]. The combination of paclitaxel and palbociclib therapy to patients with Rb + advanced breast cancer has been reported to be safe without evidence of toxicity in phase I trial [39]. However, paclitaxel also showed cardiotoxic effects [40] and exert dermatological problems to patients with gynecological organ malignancy [41].…”
Section: Resultsmentioning
confidence: 99%
“…Paclitaxel treatment resulted in apoptosis of cancer cells both In vitro and In vivo conditions [35]. The combination of paclitaxel and palbociclib therapy to patients with Rb + advanced breast cancer has been reported to be safe without evidence of toxicity in phase I trial [39]. However, paclitaxel also showed cardiotoxic effects [40] and exert dermatological problems to patients with gynecological organ malignancy [41].…”
Section: Resultsmentioning
confidence: 99%
“…In preclinical breast cancer models, when the taxane paclitaxel was given concurrently with palbociclib it showed antagonism, but showed synergy when given sequentially via intermittent dosing. 40,41 This finding can be explained by their mechanisms of action. When a CDK4/6i is administered it arrests cells in G1 which prevents cancer cells from eventually entering M phase, thereby, protecting cells from paclitaxel-induced cell death in M phase.…”
Section: Chemotherapymentioning
confidence: 92%
“…When given sequentially it is hypothesized that G1 synchronization will occur after CDK4/6i is held, allowing more cells to enter M phase and enable cell death from paclitaxel. 41 A Phase I trial with intermittent dosing in advanced breast cancer was performed and showed safety and tolerability. 41 In PCa, a phase Ib/2 clinical trial is investigating ribociclib with docetaxel and prednisone in mCRPC patients with androgen signaling inhibitor resistance and no prior chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis was that reversible G 1 arrest of palbociclib could synchronize tumor cells in the cell cycle and following their re-entry later would ensure a higher fraction in mitosis (M) phase when exposed to paclitaxel. In the first combination trial for palbociclib and paclitaxel (NCT01320592) an alternative dosing schedule was feasible and safe, without evidence of additive toxicity in Rb + breast cancer regardless of subtype (75). Phase I follow-up trial (NCT02599363) of ribocilcib and weekly paclitaxel is in progress in patients with Rb + advanced breast cancer.…”
Section: In Combination With Ddr-hrr Pathway Inhibitorsmentioning
confidence: 99%